Efektifitas Pemberdayaan Al-Qur’an Dalam Metode Qiro’ah Sab’ah - Darun Naja, anang; Rohman, Miftakhul (Universitas Nahdlatul Ulama Blitar, 2023)
This research describes a new model in learning the Koran that connects the tajwid sab'ah method with digital media. It aims to explain how the integration of technology in the Sab'ah method of reciting the Koran can maintain tradition, increase effectiveness, and optimize the use of digital media. The research method used is a combination of literature study and qualitative analysis. The results of this research show that the relationship between technology in reciting the Koran with the Sab'ah method provides significant benefits in maintaining tradition. By using special applications and software, Quran readers can engage themselves in the Sab'ah method more efficiently and accurately. In addition, technology integration can also increase learning effectiveness by providing interactive features, such as emphasizing tajwid, translation, and additional notes that make it easier to understand and memorize. The application of digital media in the recitation of the Al-Quran by the Sab'ah method also optimizes the reading experience. Through mobile applications and online platforms, users can easily access the Al-Quran anywhere and anytime. Digital media also allows users to share their experiences, notes and understandings with other reading communities, expanding their reach and supporting collaboration in learning and practicing Al-Quran recitation. This study concludes that the integration of technology in the Sab'ah method of reciting the Koran provides great potential in maintaining tradition, increasing effectiveness, and optimizing digital media. However, it is important to note that traditional values ​​and spirituality remain the main foundation in Al-Quran recitation, and technology only serves as a tool to support the learning process